INCREASING EFFICIENCY OF SOIL BIOREMEDIATION - Irina V. Kokunova; Alexander A. Zhukov; Tatyana E. Fyodorova-Semyonova (Siberian Journal of Life Sciences and Agriculture, 2022)
The intensification of agricultural production and processing industries, the use of powerful tractors and harvesters, and the increase in the intensity of road cargo transportation lead to an increase in waste from economic activities and an increase in the anthropogenic load on the environment. Human-made accidents exacerbate the problems of the stability of natural ecosystems. Dangerous substances get into the soil and accumulate in it in the form of various toxicants. This situation poses a threat to all living organisms. One of the ways to solve the urgent problems of environmental safety and the production of high-quality agricultural products is the use of bioremediation technologies for soil purification. The paper aims to increase the efficiency of soil bioremediation technology by improving the technical means used for the aeration of soil piles. The current aerators-mixers perform soil agitation and grinding of large soil formations while saturating the treated material with oxygen. We propose improving the stirring drum design of a semi-suspended aerator-mixer, equipping it with new knife-shaped working blades and with a screw winding that allows increasing the contact area with the processed mass and forming a pile of a given shape. The contact surface increases due to biological products sprayed by the nozzles and the fine soil fraction formed after treatment. This fact also intensifies the microbiological processes of toxicant oxidation. Based on the theoretical research and multivariate regression analysis, we obtained a regression equation. It allowed us to establish the relationship between the main factors that affect the aeration process of soil piles to a greater extent. We carried out experimental studies in the scientific laboratories of the university. Thus, we determined the rational parameters of the improved aerator-mixer of piles.